Investigations into the Rock Dynamic Response under Blasting Load by an Improved DDA Approach - Biting Xie; Xiuli Zhang; Hao Wang; Yuyong Jiao; Fei Zheng (Advances in Civil Engineering)
Evaluation of blasting-induced rock damage and fragmentation is very important for safety control of construction in the jointed rock mass. The discontinuous numerical models are commonly applied due to the advantages in modeling fragmentation and treating discontinuities. In this paper, the rock fracturing algorithm and rate dependent strength law are incorporated into the discontinuous deformation analysis (DDA) to study the wave propagation and rock fragmentation phenomena in dynamic problems. By reproducing Hopkinson pressure bar tests under different loading rates, the improved method is validated to be capable of solving dynamic failure problem. Finally, taking the Xiucun tunnel as an example, its failure process under the action of the explosive wave is simulated, and some failure features are captured. In addition, the explosion wave propagation and its induced particle vibration in surrounding rock are studied. The reasonable simulation results indicate that the modified DDA method can effectively model the stress wave propagation and joint growth process in the jointed rock under blasting load.